Ketogenic diet reduces a neurobiological craving signature in inpatients with alcohol use disorder - Wiers, Corinde E.; Manza, Peter; Wang, Gene-Jack; Volkow, Nora D. (Frontiers in Nutrition, 2024)
Background and Aims: Increasing evidence suggests that a ketogenic (high-fat, low-carbohydrate) diet (KD) intervention reduces alcohol withdrawal severity and alcohol craving in individuals with alcohol use disorder (AUD) by shifting brain energetics from glucose to ketones. We hypothesized that the KD would reduce a neurobiological craving signature when individuals undergoing alcohol detoxification treatment were exposed to alcohol cues. Methods: We performed a secondary analysis of functional magnetic resonance data of 33 adults with an AUD who were randomized to a KD (n=19) or a standard American diet (SA; n=14) and underwent three weeks of inpatient alcohol detoxification treatment. Once per week, participants performed an alcohol cue-reactivity paradigm with functional magnetic resonance imaging. We extracted brain responses to food and alcohol cues and quantified the degree to which each set of brain images shared a pattern of activation with a recently established ‘Neurobiological Craving Signature’ (NCS). We then performed a group-by-time repeated measures ANOVA to test for differences in craving signature expression between the dietary groups over the three-week treatment period. We also correlated these expression patterns with self-reported wanting ratings for alcohol cues. Results: For alcohol relative to food cues, there was a main effect of group, such that the KD group showed lower NCS expression across all three weeks of treatment. The main effect of time and the group-by-time interaction were not significant. Self-reported wanting for alcohol cues reduced with KD compared to SA but did not correlate with the NCS score. Conclusions: A ketogenic diet reduces self-reported alcohol wanting, and induced lower NCS to alcohol cues during inpatient treatment for AUD. However, in the KD group alcohol wanting continued to decrease across the three weeks of abstinence while the NCS scores remained stable, suggesting that this cue-induced NCS may not fully capture ongoing, non-cue-induced alcohol desire.